The Influence of Intrinsic Motivation, Organizational Culture, and Non-Physical Work Environment on Employee Performance at PT. Sriwijaya Media Partners - Farrel Fikri Hamzah; Ahmad Cik; Melati; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of Intrinsic Motivation, Organizational Culture, and Non-Physical Work Environment on Employee Performance at PT Sriwijaya Mitra Media. The analytical method used in this study is descriptive analysis method and inferential analysis with multiple linear regression assisted by the Statistical Product and Service Solution (SPSS) version 23. The data used in this Research is primary data and then distributed in the form of questionnaires to 103 employees at PT. The results of the analysis of multiple linear regression in this study that Intrinsic Motivation Variables (X1), Organizational Culture (X2) and Non- Physical Work Environment (X3) have a positive and significant effect on employee performance (Y) at PT. Sriwijaya Mitra Media. It is hoped that the result of study can improve employee performance at PT. Sriwijaya Mitra Media.